Evaluation of in Vitro Cytotoxic and Apoptotic Effect of Tarantula Cubensis Alcoholic Extract on Human Prostate Cancer Cells - Gul, Deniz; Cimen, Haci Ibrahim; Deveci Ozkan, Asuman; Guney Eskiler, Gamze; Cakiroglu, Huseyin; Atik, Yavuz Tarik; Erdik, Anil; Kose, Osman; Saglam, Hasan Salih; Gokce, Ahmet (European Journal of Therapeutics, 2023)
Objective: Prostate cancer (PCa) is the second most common cancer in men worldwide and few studies have been reported investigating the effects of homeopathic therapy on PCa. Tarantula cubensis alcoholic extract (TCAE), is used in veterinary medicine as homeopathic medicine and there are various studies about the therapeutic efficacy of TCAE in treating different diseases. However, studies about the efficacy of TCAE in cancer treatment are limited. It aimed to investigate the therapeutic efficacy of TCAE, which is used as homeopathic medicine in PCa. Methods: DU-145 and LNCaP cells were used as PCa cell lines, and HUVEC cells were used as control cell lines. The effect of TCAE (25, 50, 100 and 250 µM) on cell viability was evaluated by Water Soluble Tetrazolium Salts-1 (WST-1) analysis, and its apoptotic effects were assessed by Annexin V analysis and acridine orange staining. Results: TCAE decreased the viability rates in DU-145 and LNCaP cells in a time-dependent manner (p<0.01). The lowest viability rates for DU-145 and LNCaP cells were determined as 62.76±4.21% and 55.68±1.84% at 250 and 25 μM doses, respectively, for 48 h (p<0.01). Moreover, TCAE did not induce any cytotoxic effect on HUVEC cells (p<0.01). Apoptotic cell rates were found as 30.45±0.78% and 45.02±1.32% in DU-145 and LNCaP cells at 250 and 25 μM TCAE, respectively (p<0.01). Furthermore, impaired cell/cytoplasm ratio, chromatin condensation, membrane blebbing, and vacuolar damage were observed in DU-145 and LNCaP cells. Conclusion: TCAE exerts cytotoxic and apoptotic effects on PCa cells. Additionally, due to androgen receptor status, LNCaP cells were more sensitive than DU-145 cells. However, further molecular studies are needed to determine the potential of TCAE as a new chemotherapeutic agent in PCa.